Māyāvī mastaka, athavā, Sāhasanī pratimā : adbhuta rasamaya sacitra navalakathā - Rhoidēs, Emmanouēl D., 1835-1904 (SAMP early 20th-century Indian books project ;, 1924)
Translation from Pope Joan, English translation.